L’« hiver du mécontentement » de 1978-1979 : du mythe politique à la crise interne du mouvement travailliste - Marc Lenormand (Revue Française de Civilisation Britannique)
The 1978-1979 « winter of Discontent » has now been thoroughly analysed as a political myth through which the industrial disputes of the winter 1978-1979 were defined as the sure sign of a larger crisis of state authority and of the social-democratic management of the economy, thus helping usher in the Conservatives’ neoliberal agenda. This paper highlights a series of dynamics running through the whole decade 1970-1979, which led to the industrial disputes of 1978-1979 pitting trade unions against a Labour government, thereby revealing the fracturing of the alliance between the industrial and political wings of the UK Labour movement. These dynamics are the internal transformation of the trade union movement, the evolving relation between trade unions and government in opposition then in power, and finally the increasing divide between left and right within the party as the leadership of the party rejected the calls for an Alternative Economic Strategy and introduced strict limits on public spending and wage increases in the second half of the decade. The « winter of Discontent » can therefore best be conceived as a stage, albeit climactic, in the process of resolving the internal crisis of Labour, which took the form of « modernisation » and a shift to the centre from the mid-1980s.